Thin Film Crystal Growth Template Removal: Application to stress reduction in Lead Zirconate Titanate Microstructures - Gkotsis, P.; Kirby, Paul B.; Saharil, F.; Oberhammer, J.; Stemme, G. (American Institute of Physics (AIP), 2007)
A key issue for the design and reliability of microdevices is process related; residual stresses in the thin films from which they are composed, especially for sol-gel deposited Pb(Zrx,Ti1-x)O3 ceramics, where use of Pt as a template layer, though essential for the nucleation of the perovskite phase, results in structures with high levels of stress largely fixed by the thermal expansion coefficient mismatch between Pt and Si. Here a technique for the elimination of this stress is presented, involving the use of adhesive wafer bonding and bulk micromachining procedures to remove the Pt layer following the Pb(Zrx,Ti1-x)O3 deposition.